Factors influencing employee engagement in a financial institution in Kuala Lumpur - Mohd Hadi Alya, Mohd Rodzi (2020)
Employee engagement is properly seen as the key to efficiency. This is because employees who fully engaged with their working job and organization will enhance the unity of the workplace and motivate other employees to perform well. The objective of this study was to examine the relationship between transformational leadership, employee voice, training and development, and employee engagement among employees in a financial institution in Kuala Lumpur, Malaysia. Social exchange theory (SET) was utilized in explaining the relationship between the research variables in the research framework. The quantitative research method has been used through a questionnaire. A total of 259 employees from financial institution representing a response rate of 86% participated in this study has been collected. Three hypotheses were tested using SPSS 25. The findings indicated that transformational leadership and training and development were significant and positively related to employee engagement. The implication of this study is that organization should recruit and hire a suitable leader that has the transformational leadership style and provide relevant training programs for an employee to enhance employee engagement in the organization. Future research on others that might influence employee engagement such as compensation, organizational culture, career growth, supervisor and subordinate relationship, and work-life balance needs to be carried out.